ESTIMASI PERBANDINGAN KARBONDIOKSIDA DALAM BATANG DAUN DAN AKAR Rhizophora mucronata DI DESA SEDAYU LAWAS KECAMATAN BRONDONG KABUPATEN LAMONGAN - Muhammad Gufron (Jurnal Kelautan, 2012)
The increasing of CO2 on the atmosphere is one of the causes of global warming. The other factor of global warming is the unbalance between the emission of glass house gas on the atmosphere and the absorbtion of the ﬂora Mangrove forest are the place where a group of trees which have biologic activities such as photosynthesis and respiration. The purpose of this research is to know the biomass of Rhizophora  mucronata on the root, stem, and leafs, and to know the number of CO2 which is absorbed by the root, stem and the leafs in Rhizophora mucronata in Sedayu Lawas village Brondong, Lamongan. The result of the calculation of the biomass and the carbon by using allometric equivalence for the Rhizophora mucronata of the mangrove in the class of the diameter about 0.44-8.8 cm, it is gotten the biomass of stem Y=1.070 (DBH), for the leafs biomass Y=0.853 (DBH), and for the root's biomass Y=1.173 (DBH). The total of the CO2 in the stem is 14.82 kg/ha, on the leafs is 22.96 kg/ha and on the root is 129.03 kg/ha. Based on the analysis, the content of the carbon which is absorbed by the root is larger than the carbon which is absorbed by the leafs and the stem. The closest value is owned by the leafs and the root it is supponed by the content of the N which is large (1.26%) with the average of pH content 9.225, C-organic content 3.7%, and C/N ratio content 2.94.Keywords : Rhizophora mucronata, Sedayu Lawas, CO2